Nitrogen-rich hyper-crosslinked polymers for low-pressure CO2 capture - Fayemiwo, Kehinde A.; Vladisavljević, Goran T.; Nabavi, Seyed Ali; Benyahia, Brahim; Hanak, Dawid P.; Loponov, Konstantin N.; Manovic, Vasilije (Elsevier, 2017)
A series of poly[methacrylamide-co-(ethylene glycol dimethacrylate)] (poly(MAAM-co-EGDMA)) porous polymeric particles with high CO2-philicity, referred to as HCP-MAAMs, were synthesised for CO2 capture. The polymers with a MAAM-to-EGDMA molar ratio from 0.3 to 0.9 were inherently nitrogen-enriched and exhibited a high affinity towards selective CO2 capture at low pressures. A techno-economic model based on a 580 MWel supercritical coal-fired power plant scenario was developed to evaluate the performance of the synthesised adsorbents. The presence and density of NH2 moieties within the polymer network were determined using Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The thermogravimetric analysis (TGA) showed that the polymers were thermally stable up to 515–532 K. The maximum CO2 adsorption capacity at 273 K was 1.56 mmol/g and the isosteric heat of adsorption was 28–35 kJ/mol. An increase in the density of amide groups within the polymer network resulted in a higher affinity towards CO2 at low pressure. At a CO2:N2 ratio of 15:85, CO2/N2 selectivity at 273 K was 52 at 1 bar and reached 104 at ultra-low CO2 partial pressure. The techno-economic analysis revealed that retrofitting a HCP-MAAM-based CO2 capture system led to a net energy penalty of 7.7–8.0%HHV points, which was noticeably lower than that reported for MEA or chilled ammonia scrubbing capture systems. The specific heat requirement was superior to the majority of conventional solvents such as MDEA-PZ and K2CO3. Importantly, the economic performance of the HCP-MAAM retrofit scenario was found to be competitive to chemical solvent scrubbing scenarios.
Keywords: Amine and amide groups; CO2 solid absorbent; Hyper-crosslinked polymeric particles; Methacrylamide; Carbon capture and storage; Post-combustion CO2 capture